Combating Loneliness With Nostalgia: Nostalgic Feelings Attenuate Negative Thoughts and Motivations Associated With Loneliness - Abeyta, Andrew A.; Routledge, Clay; Kaslon, Samuel (Frontiers in Psychology, 2020)
Loneliness is difficult to overcome, in part because it is associated with negative social cognitions and social motivations. We argue that nostalgia, a positive emotional experience that involves reflecting on cherished memories, is a psychological resource that regulates these maladaptive intrapsychic tendencies associated with loneliness. We tested this hypothesis across 4 studies. Study 1 examined whether nostalgia mitigates the inverse relation between loneliness and social-confidence. Studies 2, 3, and 4 examined nostalgia’s potential to mitigate the inverse relation between loneliness and approach-oriented social goals and intentions. The results provided support that nostalgia mitigates reduced social-confidence and low approach-oriented social goals/intentions associated with loneliness. The associations between loneliness and reduced social-confidence, and loneliness and less approach-oriented social goals/intentions, respectively, were found to be weaker as a function of nostalgia. This weakening appeared to be due to nostalgia’s positive effect on social-confidence, and approach-oriented social goals/intentions, respectively, particularly at high levels of loneliness.